"The Boy Who Wasn't Really Killed": Israeli State Violence in the Age of the Smartphone Witness. (November 2021) - Stein, Rebecca L.
Abstract: Over the course of the first two decades of the twenty-first century, within the occupied Palestinian territories, photographic technologies and image-oriented politics would grow increasingly central as activist and human-rights tools of bearing witness to Israeli state and settler violence. This essay investigates the Israeli right-wing and international Zionist response to these Palestinian visual archives and their perceived threat. In particular, it tracks the rise and normalization of a repudiation script that impugned the veracity of these images, arguing that they were fraudulent or manipulated to produce a damning portrait of Israel. Drawing on post-colonial and settler-colonial studies, as placed into dialogue with digital media studies, the essay focuses on three cases studies of repudiation (2000, 2008, 2014, respectively) to consider how the long colonial history of repudiation in the Israeli context would be progressively updated by right-wing Israelis and their international supporters to meet the challenges posed by the smartphone age. By the second decade of the twenty-first century, the script had become an increasingly standard Zionist response to viral images of Palestinian death or injury at Israeli state or settler hands. Repudiation was thus marshaled as a solution to the viral visibility of Israeli state violence by bringing the otherwise damning images back into line with dominant Israeli ideology, a process of shifting the narrative from Palestinian injury to Israeli victimhood. The story of the "false" image of Palestinian injury endeavors strips the visual field of its Israeli perpetrators and Palestinian victims, thereby exonerating the state. Or such is the nature of this digital fantasy in the Israeli colonial present.